The Crack in the Cornerstone: Victorian Identity Conflicts and the Representation of the Sepoy Mutiny in Metropolitan and Anglo-Indian Novels - Flaminia Nicora (Cahiers Victoriens et Edouardiens)
In 1897, Hilda Gregg wrote from the pages of Blackwood’s Magazine that “Of all the great events of this century, as they are reflected in fiction, the Indian Mutiny has taken the firmest hold on the popular imagination.” The Mutiny was made a Victorian icon of the “British character”, conveyed by all sorts of media. The novels focusing on the event developed a specific chronotope and a subgenre—the Mutiny novel—which largely contributed to shaping national identity, confirming racial and sexual stereotypes. However, if on the one hand the Mutiny novels show how the event played a significant role in building British national identity and imperialist attitudes, they also reveal that this same notion of British identity was built on exclusions and power conflicts which divided the supporters of the imperial adventure, besides opposing them to natives. Anglo-Indians resented the ambiguity of their double status of heroes and exploiters and often tried an ante litteram “writing back”. The working class was silenced and only one novel portrays the role and point of view of simple soldiers in the Mutiny. The purpose of this article is to outline the differences of perspectives on the event and its causes, shown by novels written by “metropolitan” writers and by members of the Anglo-Indian community, officers and civil servants, who were not professional novelists, but were often eye-witnesses of the Mutiny. Attention will also be paid to class conflicts and to their representation in the Mutiny novel, as much as to other “inconsistencies” shown by narrative in the hegemony definition of roles.